Functional neurosurgery : the essentials - Brown, Jeffrey A.; Pilitsis, Julie G.; Schulder, Michael, 1957- (Thieme, 2019)
Functional neurosurgery resource features state-of-the-art approaches from renowned experts! For patients with inadequately treated epilepsy, tremor, dystonia, spasticity, depression, obsessive-compulsive disorder, Parkinson's and Alzheimer's disease, functional neurosurgery offers hope. Functional Neurosurgery: The Essentials is a reader-friendly introduction to this fascinating and rapidly evolving field. The text is edited by internationally prominent functional neurosurgeons Jeffrey A. Brown, Julie G. Pilitsis, and Michael Schulder. It features contributions from authors with expertise spa